Android-Based Pisa-Type Questions in The Ramadhan Context to Know Students' Mathematical Thinking Abilities - Suci Indah Pratiwi; Ratu Ilma Indra Putri; Somakim Somakim (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
The increasing demand for assessing students’ mathematical thinking skills in authentic and meaningful contexts, as emphasized by international assessments such as PISA, highlights the urgent need for context-based assessment instruments that are relevant to students’ everyday experiences. In response to this gap, this study aimed to develop and examine the effectiveness of a PISA-type mathematics test set grounded in a real-world context, namely Ramadan, to assess junior high school students’ mathematical thinking skills. This study employed design research in the form of a development study using Tessmer’s formative evaluation model, which included expert review, one-to-one trials, and small-group trials. The research participants were eighth-grade students at SMP IT Al-Furqon Palembang. The developed assessment package consisted of 15 PISA-type mathematics items, test blueprints, item cards, and analytic scoring rubrics. Content, construct, and language validity were evaluated through expert reviews, while clarity and comprehensibility were examined through one-to-one trials with students. Practicality was assessed using a student questionnaire administered during the small-group trial. The results indicate that the developed test items achieved a high level of validity based on expert judgments and were considered practical, easy to understand, and effective to use by students. These findings suggest that the Ramadan-contextualized PISA-type test set is suitable for use as an assessment tool to support mathematics learning and evaluation at the junior high school level. The novelty of this study lies in the integration of a culturally meaningful religious context into PISA-type mathematics assessment, demonstrating how local and contextual values can be systematically embedded to enhance the relevance, validity, and pedagogical potential of mathematical thinking assessments.